Metataxonomic analysis of microbiota from Pakistani dromedary camelids milk and characterization of a newly isolated Lactobacillus fermentum strain with probiotic and bio-yogurt starter traits - Aziz, Kanwal; Farooq, Zubair; Tariq, Muhammad; Zaidi, Arsalan Haseeb (Folia microbiologica, 2021)
This study was undertaken to investigate the starter and probiotic potential of lactic acid bacteria isolated from dromedarian camel's milk using both culture-dependent and -independent approaches and metataxonomic analysis. Strains of lactic acid bacteria recovered were examined in vitro for tolerance to gastric acidity, bile, and lysozyme. Bile salt hydrolysis, serum cholesterol-lowering, oxalate degradation, proteolytic activity, exopolysaccharide production, and cell surface characteristics necessary for colonizing intestinal mucosa were also evaluated. A single strain of the species, Lactobacillus fermentum named NPL280, was selected through multivariate analysis as it harbored potential probiotic advantages and fulfilled safety criteria. The strain assimilated cholesterol, degraded oxalate, produced exopolysaccharides, and proved to be a proficient alternate yogurt starter with good viability in stored bio-yogurt. A sensorial analysis of the prepared bio-yogurt was also found to be exemplary. We conclude that the indigenous L. fermentum strain NPL280 has the desired traits of a starter and adjunct probiotic culture for dairy products.
Keywords: velbloudi; Probiotics; mléko; Camelus; Microbiota; Limosilactobacillus fermentum; jogurt; Yogurt; zvířata; Animals; Milk; Pakistan; mikrobiota; Pákistán; probiotika